Toxaphene Agricultural Insecticides - Hercules Incorporated (1951 Hercules Advertisements, 1951)
Printed advertisement for toxaphene depicts a book with the title Toxaphene Agricultural Insecticides with an airplane spraying insecticide on a farm. This advertisement appeared in Agricultural Chemicals. Originally trademarked by the Hercules Powder Company, Toxaphene was a synthetic organic insecticide toxicant primarily used in agricultural insecticides. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Toxaphene; Chemical industry; Research, Industrial; Hercules Incorporated; Corporations; Naval stores; Insecticides; Advertising, Industrial